Assessing factors of endothelial vascular dysfunction in patients with primary open-angle glaucoma (Ukrainian Journal of Ophthalmology, 2025)
Background: Glaucoma is a leading cause of visual disability and irreversible blindness worldwide, and significantly affects quality of life. An improvement in the early diagnosis and prevention of primary glaucoma has a special value due to increasing social significance of the disease.Purpose: To investigate the value of the factors affecting vascular endothelium (oxidative stress, complement components and blood lipid profile) in patients with primary open-angle glaucoma (POAG).Material and Methods: Ninety two patients (age, 65 to 80 years) with POAG and 30 controls (somatically healthy individuals of a similar age and no known eye disease) were included in the study. They underwent an eye examination including visual acuity, Maklakoff tonometry, non-contact tonometry, biomicroscopy, gonioscopy, and pachymetry. Plasma lipid peroxidation and antioxidant activity levels, blood lipid composition and blood C3 and C5a levels were assessed.Results: Blood malondialdehyde (MDA) levels in patients with POAG were 87% higher compared to controls. Blood C3 levels in patients with POAG were 18% higher compared to controls. The C5a complement is a multicomponent plasma enzyme system that exhibits lysis and opsonization functions during activation. Blood C5a levels were 6 times higher in patients with POAG than in controls (13.86 ± 0.44 mg/scale division versus 2.33 ± 0.11 mg/scale division).Conclusion: Increased C5a activity, hypersecretion of active oxygen species (in the presence of insufficiently efficacious antioxidant system of blood), and increased atherogenic plasma index (in the presence of low levels of high-density lipoproteins) are a mechanism of endothelial dysfunction in POAG. We found an imbalance between the prooxidant and antioxidant systems, abnormal composition of blood lipids (e.g., hypercholesterolemia and hypertriglyceridemia) and elevated C5a levels in patients with POAG.
Keywords: primary open-angle glaucoma; lipid peroxidation; antioxidant system; complement components; blood lipid composition